2008
DOI: 10.1002/elps.200700784
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance and alteration of genome methylation in F1 hybrid rice

Abstract: We analyzed the inheritance of DNA methylation in the first filial generation(F1) hybrid of Oryza sativa L. ("Nipponbare"x"Kasalath") by restriction landmark genome scanning (RLGS). Most parental RLGS spots were found in the F1, but eight spots (4%) showed abnormal inheritance: seven of the eight spots were missing in the F1, and one was newly detected in the F1. Here we show demethylation at restriction enzyme sites in the F1. We also found a candidate site of stable heterozygous methylation in the genome. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…The methylation pattern of reciprocal cross F1 generation have four types, namely monomorphism, demethylation, hypermethylation and hypomethylation, but they are mainly composed of type hypermethylation. This conclusion is basically identical to the research conclusion of Wang [33], but is not the same finding in corn, Arabidopsis thaliana [12,39], larch [34] and rice [40]. Related studies [34] have shown that methylation means that genes translate from activation to suppression; however, demethylation means that genes translate from suppression to activation.…”
Section: Discussionsupporting
confidence: 80%
“…The methylation pattern of reciprocal cross F1 generation have four types, namely monomorphism, demethylation, hypermethylation and hypomethylation, but they are mainly composed of type hypermethylation. This conclusion is basically identical to the research conclusion of Wang [33], but is not the same finding in corn, Arabidopsis thaliana [12,39], larch [34] and rice [40]. Related studies [34] have shown that methylation means that genes translate from activation to suppression; however, demethylation means that genes translate from suppression to activation.…”
Section: Discussionsupporting
confidence: 80%
“…The methylation status of the parental Nipponbare and Kasalath, 9 NKF 1 plants (NK1 to NK9), and 9 KNF 1 plants (KN1 to KN9) was analyzed by an RLGS method with combinations of Not I– Msp I– Bam HI (hereafter [ Msp I] pattern) or Not I- Hpa II- Bam HI ([ Hpa II] pattern) restriction enzymes [22, 25]. Briefly, 0.4  μ g of genomic DNA was treated with 2 U DNA polymerase I (Nippon Gene, Tokyo, Japan) in 10  μ L of blocking buffer (10 mM Tris-HCl, pH 7.4, 10 mM MgCl 2 , 1 mM dithiothreitol (DTT), 0.4  μ M dGTP, 0.2  μ M dCTP, 0.4  μ M ddATP, and 0.4  μ M ddTTP) at 37°C for 20 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…indica cv. Kasalath by RLGS, and detected altered inheritance and demethylation of specific RLGS spots in F1 plants [25]. In this study, we analyzed the appearance or disappearance of two altered spots in reciprocal F1 hybrids and selfed progeny, and detected an unexpected allelic expression bias.…”
Section: Introductionmentioning
confidence: 96%
“…If so, all isolated Hpa II fragments of the (-, +) MH type should contain at least one additional internal CCGG site; indeed, this was reported for all such sequenced fragments [41]. Internal CCGG sequences were also identified in Hpa II-specific fragments obtained from restriction landmark genome scanning of A. thaliana and rice, and their CmCGG methylation status was confirmed by Southern blot hybridization and/or by polymerase chain reaction (PCR) [42,43]. More evidence for the presence of internal CmCGG site(s) in the fragments of the (-, +) MH type comes from MSAP analysis of seven swine tissues where approximately 26.2% and 25.7% of MH patterns were of the (+, -) and (-, +) type, respectively [21].…”
Section: Resultsmentioning
confidence: 89%